Problems Of The Mplementation Of The Package C Equality Program In The Non-Formal Education Unit (SPNF) Sanggar Learning Activities (SKB) Merangin Regency - Iswandi Iswandi; Afrinovera Afrinovera; Asul Dewi Fikra (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2022)
This research is motivated by the existence of students and tutors who behave less disciplined, this can be seen from the delay in coming during the learning process, as well as students who are busy with their work so that they cannot follow the lesson. This study uses a qualitative method. The results of the study show that there are three preparations that must be made so that the program runs well, namely planning, implementation and evaluation. While the assessment is given full authority to the tutor based on the presence of students. The solution taken by the manager is to provide motivation, approach and a clearer understanding of equality education in order to achieve the program objectives that have been designed.Keywords: Program Implementation, Package C equivalency education.